Mapping onshore wind turbine generators in Italy from Sentinel-2 data - Aiello, Martina; Airoldi , Davide; Garofalo, Elisabetta (GEOmedia, 2022)
Resources availability assessment is essential for renewable energy planning and related development scenarios for the achievement of decarbonisation objectives. As national information about wind farm projects often lack a geographic connotation, the definition of a rapid and extensive approach for mapping installed wind turbines is a priority. The currently available free medium resolution satellite data considerably facilitate WTGs localization and represent a valid instrument to retrieve input data to models and applications for renewable energy sources spatial planning.